Identification and characterization of pbpC, the gene encoding Bacillus subtilis penicillin-binding protein 3. - Murray, T (1996)
Penicillin-binding proteins (PBPs) are enzymes involved in the synthesis of peptidoglycan structures in Bacillus subtilis such as the vegetative cell wall and the spore cortex. The B. subtilis sequencing project has identified a gene (orf16, EMBL accession number D38161) which exhibits significant sequence similarity to genes encoding class B high-molecular-weight PBPs. We have found that orf16 encodes PBP3 and have renamed this locus pbpC. Transcriptional fusions to lacZ were used to demonstrate that pbpC is transcribed primarily during log-phase growth, with lower amounts expressed during sporulation. During spore germination and outgrowth, pbpC expression resumes coincident with an increase in the optical density of the culture. The major promoter for pbpC is located just upstream of the gene; a low level of expression during sporulation appears to originate from much further upstream. Loss of PBP3 does not produce any detectable change in phenotype with respect to cell morphology, growth, sporulation, spore heat resistance, or spore germination and outgrowth. This was also true when the pbpC mutation was combined with mutations affecting other PBP-encoding genes to produce double mutants. These findings are consistent with previous evidence that many PBPs of B. subtilis have redundant functions within the cell.